Measuring the Prevalence of Chronic Kidney Disease among Type 2 Diabetes Mellitus Patient in Hospital Jitra: A Population-Based Cohort Study - Norazila Abdul Ghani; Sharifah Nor Faiza Syed Hassan; Rusyidah Zainol Abidin; Zarmisha Zakaria; Fatin Farhana Ahmad Nasir; Ahmad Zulfitri Azmi (Journal of Pharmacy, 2025)
Introduction: Chronic kidney disease (CKD) develops in approximately 40% of patients with diabetes. The prevalence of CKD in Malaysia is 9.07% among adults. It is important to obtain accurate local data on CKD among patient with Type 2 Diabetes Mellitus (T2DM) patients to facilitate health-care planning including the review of health-care priorities, program activities, and allocation of resources. The objective of this study is to determine the prevalence of CKD among DM. We further explored the association between glycaemic control, eGFR and adverse outcomes (cardiovascular events, hospitalizations, and kidney failure) among these patients. Materials and method: This is a retrospective cohort study involving 91 DM patients who received treatment in Hospital Jitra, Kedah, Malaysia. Patients’ demographic data, comorbidities, history of hospital admission, medications, complication, and laboratory test results were retrieved from their medical record. Descriptive and inferential statistics have been used to analyse the data. Results: 60.4% of the patients were female and 85.7% Malay with mean age of 62.15 years old. Hypertension, hypercholesterolemia and heart disease were the most common comorbidities among them; 92.3%, 78.0%, and 23.1%, respectively. The prevalence of CKD among DM in Hospital Jitra was 38.46%. 20.9% of the patients experienced diabetic complications and 49.5% showed a progression of kidney disease. The results indicate a high percentage of poor glycaemic control among DM in Hospital Jitra; 69%-100% of the patients had HbA1c >7% at each visit and this is associated with CKD (P=0.042). Conclusion: The prevalence of CKD among DM patients at Hospital Jitra was 38.46%. Higher HbA1c was associated with CKD in adults with type DM, suggesting that improving glycaemic control may reduce the risk of CKD.